2014 IEEE Metrology for Aerospace (MetroAeroSpace) 2014
DOI: 10.1109/metroaerospace.2014.6865970
|View full text |Cite
|
Sign up to set email alerts
|

Noise estimate of pendular Fabry-Perot through reflectivity change

Abstract: A key issue in developing pendular Fabry-Perot interferometers as very accurate displacement measurement devices, is the noise level. The Fabry-Perot pendulums are the most promising device to detect gravitational waves, and therefore the background and the internal noise should be accurately measured and reduced. In fact terminal masses generates additional internal noise mainly due to thermal fluctuations and vibrations. We propose to exploit the reflectivity change, that occurs in some special points, to mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…To test the electromagnetic mirrors performances and the noise effective temperature [8], [9], we propose to measure the escape time from a minimum, instead of the full trajectory. In analogy with research in Josephson junctions dynamics [10] where escapes have been employed to characterize Poissonian [11] or non Gaussian noise sources [12], escape times can be also used to characterize thermal noise intensity on pendular Fabry-Perot [13]. In this work we propose to extend the application of escape times analysis to the case where a signal is embedded in noise.…”
Section: Introductionmentioning
confidence: 99%
“…To test the electromagnetic mirrors performances and the noise effective temperature [8], [9], we propose to measure the escape time from a minimum, instead of the full trajectory. In analogy with research in Josephson junctions dynamics [10] where escapes have been employed to characterize Poissonian [11] or non Gaussian noise sources [12], escape times can be also used to characterize thermal noise intensity on pendular Fabry-Perot [13]. In this work we propose to extend the application of escape times analysis to the case where a signal is embedded in noise.…”
Section: Introductionmentioning
confidence: 99%
“…(again T s = 2π/ω). It has been shown that the resulting unknown-initial-phase detector for H > 10 has nearly the same performance as (19), which applies to the coherent (known initial phase) case [4], and it is comparable to the performances of the noncoherent correlator (standard optimum benchmark detector for signals with unknown initial phase). On the other hand, the SSC-SRD is computationally extremely cheap, in that it only requires binary and/or integer arithmetics.…”
Section: B Strobed Detection Strategymentioning
confidence: 96%
“…As preeminent examples where the optimal strategy is not feasible, we can mention the cases where the full trajectory S(t) is difficult to retrieve (as in very sensitive Fabry-Perot pendulums for gravitational waves detection [18,19]), or it is just not available for measurements (as in Josephson junctions, for the quantum mechanical nature of the dynamical variable [20][21][22]). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations